Factors influencing research data communication on Zika virus: a grounded theory - Costa, Michelli Pereira da (2019)
Purpose – The purpose of this paper is to propose a theoretical model to illustrate factors influencing research data communication on diseases caused by the Zika virus. Design/methodology/approach – The grounded theory methodology was adopted. For data collection, interviews were conducted with 13 Brazilian researchers involved with the Zika virus theme. Data analysis was performed using the open, axial and selective coding processes, according to the principles of the grounded theory. Findings – Based on data collection and analysis, seven theoretical categories representing intervening factors in Zika virus research data communication were identified. The emerging theory showed the centrality of researchers’ expectations for acknowledgment and reward, influenced by the aspects of research funding and academic culture. Three factors involved in the macro processes of research data communication: data use, data production and data sharing. In the use and production processes, factors related to collaboration figured most strongly. In the production and sharing processes, the factors regarding data processing and the use of research data repositories were more pronounced. Finally, data sharing, and the possibility of reusing data are directly affected by the social context of Zika virus disease as an emerging disease. Originality/value – The study presents a theory developed systematically to explain the phenomenon of communication of research data on Zika virus. The theory presents a set of intervening factors of the process of communication of research data and discusses the factors in light of the fundamentals of information science.